Camel milk and D-allulose synergistically improved camel dairy flavor and alleviated insulin resistance of human HepG2 cells - Tuerxunnayi Aili; Zhaoxu Xu; Chen Liu; Jie Yang; Haitao Yue (Heliyon)
Camel milk is a dairy product widely consumed in desert and semi-arid areas, with high nutritional value and potential for auxiliary medical treatment. It has unique efficacy and a gamey taste, and exploring its functional factors and making camel milk more easily accepted by the public has become a research hotspot. This study mainly investigated the protein components in camel milk that may play a role in alleviating insulin resistance by observing the cell activity, glucose consumption, and morphological changes of the treatment group. Further research was conducted on the potential synergistic hypoglycemic effect of camel milk and D-allulose, and a formula was ultimately determined to enhance the flavor of camel milk through a series of sensory evaluation experiments. The optimal concentration for the treatment of insulin resistance (IR) was identified as 4 mg/mL of CWP4 combined with 1 mg/mL of D-allulose for a period of 12 h. The addition of D-allulose at a ratio of 1:36 in camel milk has been observed reduce the odoriferous properties of the camel milk, while simultaneously retaining the majority of other desirable flavors. This research helps to concentrate the functional protein factors in camel milk, promote the intensive processing of camel milk, and develop new camel milk health products. These products may help patients with diabetes stabilize their blood sugar levels in daily life, thus enriching their diet, and may expand the market of camel milk.